Age and sex differences in the cortisol stress reactivity and recovery among infants exposed to prenatal psychological distress. (January 2022) - Kortesluoma, Susanna; Korhonen, Laura S.; Pelto, Juho; Tuulari, Jetro J.; Karlsson, Linnea; Karlsson, Hasse
Abstract: Background: Altered hypothalamic-pituitary-adrenal axis (HPA) functioning is one of the potential mechanisms bridging exposure to maternal prenatal psychological distress (PPD) and later risk for offspring psychiatric illness. Research on infant cortisol stress reactivity, on scarcely studied recovery and their associations with maternal PPD is needed to clarify these mechanisms. Knowledge on sex differences in prospective settings is largely lacking. We aimed at filling these gaps by building upon our previous report showing that exposure to maternal prenatal depressive and anxiety symptoms associates with slower cortisol recovery among 10-week-old female infants. Methods: In all, 363, 205 and 263 infants at 10 weeks, six and 14 months of age from the FinnBrain Birth Cohort Study participated in a stress test comprising of venipuncture and nasopharynx sampling. Five saliva cortisol samples were collected during each visit to measure cortisol reactivity and recovery. PPD was assessed from maternal self-reports for depressive, anxiety and pregnancy-related anxiety symptoms at gestational weeks 14, 24 and 34. Results: An 11% enhanced recovery among 14-month-old females was associated with higher depressive and anxiety symptoms (95% CI = 1–23%) and pregnancy-related anxiety symptoms (2–21%). No alterations in the female cortisol reactivity or male cortisol stress responses were observed. Conclusions: The opposite directions in the associations between the PPD exposure and infant cortisol recovery among 10-week-old and 14-month-old females suggest sex- and age-dependent associations between HPA axis functioning and PPD exposure among healthy infants. Follow-up is needed to characterize the impact of this altered negative feedback mechanism on later health. Highlights: Cortisol stress recovery differed by sex and age in prenatal distress exposed infants. We observed faster cortisol recovery in females at the age of 14 months. We have previously observed slower female cortisol recovery at 10 weeks of age. Recovery could be more sensitive to the prenatal distress exposure than reactivity. In addition to stress reactivity, cortisol recovery has predicted psychiatric disorders.